2021
DOI: 10.1210/clinem/dgab892
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Therapeutic Role of Vitamin D in COVID-19: Systematic Review and Meta-analysis

Abstract: Purpose Vitamin D deficiency/insufficiency may increase the susceptibility to COVID-19. We aimed to determine the association between vitamin D deficiency/insufficiency and susceptibility to COVID-19, its severity, mortality and role of vitamin D in its treatment. Methods We searched CINHAL, Cochrane library, EMBASE, PubMED, Scopus, and Web of Science up to 30.05.2021 for observational studies on association between vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(115 citation statements)
references
References 70 publications
6
106
0
3
Order By: Relevance
“…However, for some of them, such as vitamin D, diet alone cannot increase serum 25 (OH) D concentrations to provide optimal protection from SARS-CoV-2. In addition, further randomized trials with an early administration of high doses of vitamin D after the onset of COVID-19 should be conducted in order to identify the right time to start vitamin D administration to achieve a significant effectiveness [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, for some of them, such as vitamin D, diet alone cannot increase serum 25 (OH) D concentrations to provide optimal protection from SARS-CoV-2. In addition, further randomized trials with an early administration of high doses of vitamin D after the onset of COVID-19 should be conducted in order to identify the right time to start vitamin D administration to achieve a significant effectiveness [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bolus vitamin D supplementation also was associated with decreased mortality in hospitalized COVID-19 patients in Turkey [ 20 ], and an improved 3-month survival in geriatric patients [ 21 ]. This information was confirmed in a meta-analysis that included data from observational and randomized controlled trials that reported reduced severity risk with higher 25(OH)D, and some benefit from vitamin D in treating COVID-19 [ 22 ].…”
Section: Introductionmentioning
confidence: 85%
“…Our previous results also showed that severe vitamin D deficiency is associated with severity and death in COVID-19 patients [ 29 ], and were comparable to recent findings [ 4 , 30 ]. Dissanayake and colleagues, whose meta-analysis included 72 COVID-19 observational and 4 interventional randomized studies, have shown not only correlations between 25(OH)D level and severity or mortality, but also some clinical benefits and improvement in inflammatory markers of vitamin D supplementation in treating COVID-19 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis involving 76 studies reported inverse correlations for COVID-19 risk with respect to serum 25(OH)D concentrations for risk of developing the disease, its severity, and risk of death [ 3 ], thus offering support for the role of vitamin D in reducing risk of COVID-19.…”
mentioning
confidence: 99%
“…However, because of the concern that having an acute inflammatory illness could lower serum 25(OH)D concentrations [ 4 ], observational studies of COVID-19 using 25(OH)D concentrations measured at or near time of diagnosis have been questioned. The data in Figure 3 of reference [ 3 ] can be used to address that concern. The 19 studies can be divided into four categories: 25(OH)D at time of diagnosis (seven studies); within 1 year prior (eight); preceding 10 years (one); and 10–15 years prior (three).…”
mentioning
confidence: 99%